Doxycycline treatment modulates the immune response of tilapia and controls Aeromonas hydrophila infection - de Oliveira, Susana Luporini [UNESP]; da Costa, Camila Carlino [UNESP]; Aracati, Mayumi Fernanda [UNESP]; Rodrigues, Leticia Franchin [UNESP]; Montassier, Hélio José [UNESP]; Conde, Gabriel; Rodrigues, Romário Alves [UNESP]; Charlie-Silva, Ives [UNESP]; Clissa, Patrícia Bianca; Pereira, Luiz Arthur Malta; de Andrade Belo, Marco Antonio (Elsevier, 2024)
The objective of this study was to evaluate the immunopharmacological activity of doxycycline, administered orally in Nile tilapia (Oreochromis niloticus), during experimental infection by Aeromonas hydrophila, through the correlation between therapeutic efficacy and fish immune response. 160 Nile tilapia (±100 g) from the same spawning were distributed in 16 tanks (100 L, n = 10), constituting four treatments: control (infected and untreated); Infected and Treated with 20, 40 and 80 mg of doxycycline/Kg of b.w. Control fish and treated with the lowest dose of doxycycline (20 mg) exhibited typical signs of aeromonosis, including exophthalmos, fin erosion, hemorrhagic septicemia, corneal opacity and ascites. No clinical signs were observed in animals treated with 40 and 80 mg of doxycycline. There was a dose-response effect to the treatment with this tetracycline with relative percentage of survival (RPS) of 60, 73.3 and 93.3% for the treatments with 20, 40 and 80 mg/kg of b.w. when compared to control animals, as well as increased in the production of antibodies anti-A. hydrophila. Doxycycline treatment decreased monocytosis and reactive oxygen species (ROS) production observed in tilapia during A. hydrophila infection. Therefore, doxycycline administered orally to O. niloticus revealed the potential of this antimicrobial for use in tilapia farming, providing convincing results of the therapeutic efficacy against A. hydrophila. These results confirm the hypothesis that the antimicrobial action of doxycycline favored the defense mechanisms of tilapia treated mainly at a dose of 80 mg/kg. Although the exact mechanism of increased antibody response remains to be elucidated, the present observations demonstrate important practical significance for the sanitary management of tilapia farming.
Keywords: Aeromonosis; Cichlids; Fish diseases; Immune response; Tetracyclines; Therapeutic efficacy